The effect of dietary fatty acid on breast cancer lipidome - Costa, Ana Cláudia Marques Lopes Soares da (2014)
Breast cancer is a complex heterogeneous disease and one of the leading causes of death among women. Many studies have tried to determine if saturated, monounsaturated and polyunsaturated fatty acids (FA) have different effects on the development of breast cancer. However, the role of different dietary FAs in lipidome of breast cancer cells is not completely understood. The aim of this work was to establish if lipidome of breast cancer T47-D cell line differs with different dietary FAs and correlate this findings to effects in proliferation and apoptosis. The lipid changes in lipidome induced by the presence of 1 μg/mL oleic acid (OA1) or 1 or 2 μg/mL linoleic (LA1 or LA2, respectively) acid in vitro were study through a lipidomic analysis, based on techniques such as TLC and GC-MS. TLC allowed the separation and quantification of Phospholipid (PL) classes and GC –MS allowed the separation and quantification of FAs. TGs and CHL were quantified. Also, cell viability and apoptosis were evaluated. PL class analysis showed significant alterations in phosphatidylethanolamine (PE), phosphatidylserine (PS) in the medium with LA1 or LA2, respectively and lysophosphatidylcholine (LPC) in the medium with OA1. GC-MS showed an increase of 18:2 in the treatment with LA. Further TG showed a decrease on LA2 treatment and viability and apoptosis assays showed that LA1 and LA2 stimulate cell growth and OA2 stimulated apoptosis, respectively. This work contributes to a better understanding of the influence of dietary FAs on the lipidome of T-47D cells and shows that alterations in cellular lipidome are associated to changes in cell number and apoptosis. These findings may lead to new perspectives in the identification of specific targets that may be helpful to understand the process behind breast cancer growth. However, more studies are necessary to conclude about how different lipid molecules promote these effects.